Social dialogue and working conditions (Dublin, 2011)
"Creating better jobs and working conditions are key elements of the European social model. Improving the quality of work and working conditions is, however, a new dimension within the European Employment Strategy which previously concentrated on quantitative measures such as increasing employment and reducing unemployment. The Lisbon Agenda implies that improving the quality and productivity of work could lead to more as well as better jobs. This study is based on 23 case studies in four sectors (electromechanical engineering, food, financial activities and insurance services, and wholesale and retail) in six countries (Austria, the Czech Republic, Germany, France, Spain and Sweden)."